Inequality and the Labor Market : The Case for Greater Competition - Harris, Benjamin H.; Block, Sharon (Book collections on Project MUSE., 2021)
For decades, falling competition in the U.S. labor market has weakened wage growth and diminished job quality. While sluggish productivity growth, rising globalization, and declining union representation are traditionally cited as factors for this historic imbalance in economic power, diminished labor market competition has had an increasingly detrimental impact on American workers. [This book] frames the legal and economic consequences of this imbalance and presents a series of urgently needed reforms for both labor and antitrust laws to improve outcomes for American workers. These include higher wages, safer workplaces, increased ability to report labor violations, greater mobility, more opportunities for workers to build power, and overall better labor protections -- publisher's description